Limnic ostracoda from Silveirinha, Portugal (? Late Paleocene - Lowermost Eocene) - Colin, J.-P. (2010)
Silveirinha, a rich site for mammals and other vertebrates, yielded some molluscs, charophytes and ostracods. The latter are described here. Eight species were recognized. Two of them, Ilyocypris lusitanicus n. sp. and Cypris silveirinhaensis n. sp. are new. Other, unnamed species may be ascribed to Cyclocypris? and Cypria? besides a further four undeterminate Cypridacea. The Ostracod association is typical for limnic environments and is compatible with intertropical conditions. Cypris silveirinhaensis suggests an Eocene, and especially a lower Eocene age.